Automatic Visual Inspection of Grains Quality In Agroindustry 4.0 - Macedo, Robson Aparecido Gomes de (2018)
With the advent of Industry 4.0, the use of new technologies, robotization and advanced manufacturing has been extended to the agricultural sector, with the aim of increasing productivity, reducing environmental impacts, increasing profits and improving the quality of products, giving rise to the terms Precision Agriculture, Agribusiness 4.0, Agriculture 4.0 and Agroindustry 4.0. If on the one hand much is being said about the adoption of new technologies in the stages of land preparation, planting and harvesting, on the other hand very little is said about the processing of agricultural products using, for example, automated systems for visual inspection of quality. This work aims to investigate the different approaches for automatic visual inspection of grains quality proposed in the last decade and present a discussion about how these approaches are inserted in the context of these new productive processes of modern agriculture, as well as the positive aspects and the limitations found for their uses.